INSUSCEPTIBILITY OF PUPS TO CHLOROFORM POISONING DURING THE FIRST THREE WEEKS OF LIFE - Whipple, G. H. (The Rockefeller University Press, 1912)
Employing the liver necrosis as an index, we find that pups are immune to the poisonous action of chloroform anesthesia. This immunity or resistance to late chloroform poisoning is complete in the first week, very striking during the second and third weeks, and usually disappears during the fourth week of life. Nests of blood-forming cells (blood islands) are numerous in the sinuses of the liver during the first week and normally become progressively less numerous each week until the liver is almost free from these cells at the end of the fourth week of life. It is considered possible that these leucocytes in the blood islands protect the liver against the specific action of a known poison (chloroform). The mechanism of this hypothetical protective action is not understood, but it may consist of a process of neutralization. Perhaps this protective action against poisons is an important part of the functions of white blood cells and may bear an important relationship to the process of inflammation.